2010
DOI: 10.1121/1.3397432
|View full text |Cite
|
Sign up to set email alerts
|

Measures of tactual detection and temporal order resolution in congenitally deaf and normal-hearing adults

Abstract: To guide the development of tactile speech aids, tactual detection and temporal order discrimination by congenitally deaf and normal-hearing adults have been examined. Tactual detection thresholds for sinusoidal vibrations between 2 and 300 Hz were measured at the left thumb and index finger using an adaptive paradigm. Temporal onset-and offset-order discrimination were tested using stimuli of 50 Hz at the thumb and 250 Hz at the index finger, delivered asynchronously and varied independently in amplitude and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
(41 reference statements)
4
15
1
1
Order By: Relevance
“…The effects of deafness on tactile abilities are highly variable. Some investigations on body perception in the deaf have reported no differences in tactile perception (see, e.g., refs [ 30 ] and [ 31 ]), while others have suggested improvements [ 32 , 33 ] or even declines [ 28 ]. Investigations on abilities closer related to the cross-arm TOJ task on movement and posture have revealed a more consistent effect of deafness.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of deafness on tactile abilities are highly variable. Some investigations on body perception in the deaf have reported no differences in tactile perception (see, e.g., refs [ 30 ] and [ 31 ]), while others have suggested improvements [ 32 , 33 ] or even declines [ 28 ]. Investigations on abilities closer related to the cross-arm TOJ task on movement and posture have revealed a more consistent effect of deafness.…”
Section: Discussionmentioning
confidence: 99%
“…Bernstein et al [ 45 ] compared the thresholds between 10Hz and 250Hz on the index finger of two children aged 9 and 10 years who were profoundly deaf with those of other children and found no significant difference. Similarly, Moallem et al [ 46 ] compared thresholds between 2Hz and 300Hz on the glabrous skin of the thumb and index finger of adults with normal hearing and those who were congenitally deaf, and found no difference. The results of the present study also support those found in two previous studies using other parts of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Levänen and Hamdorf ( 2001 ) showed better tactile change detection in deaf than in hearing participants, but found no difference between the two groups in tactile frequency discrimination. Furthermore, tactile detection thresholds were reported to be either comparable in deaf and hearing individuals (Moallem et al, 2010 ) or elevated in the deaf (Frenzel et al, 2012 ). Tactile detection, measured by response times, was comparable in deaf and hearing participants (Heimler and Pavani, 2014 ).…”
Section: Introductionmentioning
confidence: 99%